The cost to carshare: A review of the changing prices and taxation levels for carsharing in the United States 2011–2016. (July 2017) - Schwieterman, Joseph P.; Bieszczat, Alice
Abstract: This study explores the changing prices and level of taxation for carsharing in the United States through a review of hourly rates in 80 cities with Zipcar pods, as well as at U.S. locations served by car2go and Maven. The base rate for a one-hour Zipcar carshare between 2011 and 2016 is shown to have fallen from 9.39 to 8.92, a 5.0% drop. In inflation-adjusted terms, this constitutes an 11.2% real reduction. Retail taxes over the period, however, rose from 15.5% to 17.0%, offsetting almost one third of the price reduction. In some cities, taxes on one-hour reservations exceed 30% due to transaction-based fees that apply regardless of the duration of the trip. Interpreted broadly, these results indicate that carsharing is becoming more affordable to urban consumers, while being subject to extensive competition and facing the burden of extensive retail taxes that may hamper efforts to achieve local sustainability goals. Highlights: The base rate for a one-hour Zipcar carshare between 2011 and 2016 fell from 9.39 to 8.92, a 5.0% drop. In inflation-adjusted terms, this constitutes an 11.2% real reduction. Retail taxes over the period rose from 15.5% to 17.0%, offsetting almost one third of the price reduction. In some cities, taxes on one-hour reservations exceed 30% due to transaction-based fees that apply regardless of the duration of the trip. Carsharing is becoming more affordable to urban consumers, while being subject to extensive competition and facing the burden of retail taxes that are substantially higher than general sales taxes in most cities. Although the political economy of car rental taxes makes reform difficult, such efforts should be regarded as being potentially important to the achievement of local sustainability goals.